Proses berpikir siswa dalam menyelesaikan masalah geometri berdasarkan teori Van Hiele ditinjau dari gender - Iyad Mulyadi; Dedi Muhtadi (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2019)
This study aims to determine the thinking process of students in solving geometric problems based on Van Hiele's theory in terms of gender. The subjects in this study were 6th grade VII students in one of the public MTs in Pangandaran Regency, which consisted of 3 male and 3 female students, each of whom was capable of high, medium and low. The method used is qualitative research. Data collection techniques were carried out by test and interview methods. The results showed that in terms of gender high-ability male students are at level 2 (informal deduction), male students are capable of being at level 1 (analysis), while low-ability male students are at level 0 (visualization). The female students with high and moderate abilities are at level 1 (analysis), and low-ability female students are at level 0 (visualization). Keywords: Thinking process, geometry, van Hiele's theory, gender